1992
DOI: 10.1016/1010-7940(92)90188-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cardiomyoplasty for long-term cardiac assist

Abstract: The principle of cardiomyoplasty is long-term electrostimulation of a latissimus dorsi muscle (LDM) wrapped around the failing heart. Technically, this procedure consists of placing the left LDM flap around the heart via a window created by partial resection of the 2nd or 3rd rib, and subsequent muscle electrostimulation in synchrony with ventricular systole. The aim of cardiomyoplasty is to support ventricular function in ischemic or dilated cardiomyopathies, or to partially replace the ventricular myocardium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…It has been demonstrated that dynamic cardiomyoplasty (Chachques et al 1988(Chachques et al , 1992Magovern et al 1988) and dynamic graciloplasty (Baeten et al 1988;Williams et al 1990;Janknegt et al 1995) represent important medical applications for the use of transformed skeletal muscle and are increasingly used in the treatment of congestive cardiomyopathies and sphincter incontinence. Because the stimulation-induced transformation is a time-dependent process encompassing sequential fast-to-slow ®bre type transitions, it is of interest to study to what extent metabolic adaptations, preceding ®bre type transitions, contribute to confering fatigue-resistance to the stimulated muscle.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that dynamic cardiomyoplasty (Chachques et al 1988(Chachques et al , 1992Magovern et al 1988) and dynamic graciloplasty (Baeten et al 1988;Williams et al 1990;Janknegt et al 1995) represent important medical applications for the use of transformed skeletal muscle and are increasingly used in the treatment of congestive cardiomyopathies and sphincter incontinence. Because the stimulation-induced transformation is a time-dependent process encompassing sequential fast-to-slow ®bre type transitions, it is of interest to study to what extent metabolic adaptations, preceding ®bre type transitions, contribute to confering fatigue-resistance to the stimulated muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Mitral or tricuspid regurgitation should not exceed II grade, and the serum creatinine should be £2.5 mg/dl with no organs failure [3,5,14]. Moreover, it was well established that a combined DCMP and cardioverter defibrillator implantation intervention improves the survival in patients with ventricular arrhythmias [15][16].…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…The results of cardiomyoplasty in patients presenting atrial fibrillation are frequently unsuccessful (9,10,22). A permanent A-V block can be performed using interventional cardiology methods (radiofrequency catheter ablation).…”
Section: I219mentioning
confidence: 99%